2008
DOI: 10.1016/j.expneurol.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation exacerbates behavioral and histopathological consequences of isolated traumatic brain injury in rats

Abstract: The proinflammatory cytokine interleukin-1β (IL-1β) is induced rapidly after traumatic brain injury (TBI) and contributes to the inflammatory events that lead to neuronal loss. Although an important source of IL-1β is from the injured brain itself, in patients with multiple organ trauma (polytrauma) IL-1β is also released into the bloodstream which may potentially influence brain vulnerability. The purpose of this study was to determine the effects of systemic inflammation induced by peripheral administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 47 publications
2
65
1
3
Order By: Relevance
“…Notably, following TBI, circulating pro-inflammatory cytokines, such as IL-1β and TNF-α, dramatically increased within hours (18). Furthermore, it was reported that intraperitoneal injection of pro-inflammatory cytokines to experimental animals could worsen the pathological consequences of TBI (31). In the present study, plasma levels of IL-1β and TNF-α within 24 h of CCI injury were significantly elevated, and these levels were significantly decreased by TMP.…”
Section: Discussionsupporting
confidence: 50%
“…Notably, following TBI, circulating pro-inflammatory cytokines, such as IL-1β and TNF-α, dramatically increased within hours (18). Furthermore, it was reported that intraperitoneal injection of pro-inflammatory cytokines to experimental animals could worsen the pathological consequences of TBI (31). In the present study, plasma levels of IL-1β and TNF-α within 24 h of CCI injury were significantly elevated, and these levels were significantly decreased by TMP.…”
Section: Discussionsupporting
confidence: 50%
“…These effects are independent of core body and brain temperature (Parry-Jones et al, 2008). Systemic inflammation also sensitizes the brain to neonatal hypoxic and hemorrhagic injury (Lehnardt et al, 2003;Xue and Del Bigio, 2005) and exacerbates excitotoxic (Favrais et al, 2007) and traumatic brain injury (Utagawa et al, 2008). The clinical relevance of these findings is underlined by epidemiological and clinical studies demonstrating that systemic infection is a risk factor for stroke and that preceding infection is associated with less favorable outcome (Emsley and Hopkins, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 It is probable that the acute systemic inflammatory response triggered by surgery initiates or exacerbates ischemic cerebral injury. Laboratory studies using sepsis models in conjunction with neurologic injury 22,23 and clinical studies demonstrate more severe neurologic deficits, especially when preceded by respiratory and urologic infections. 24 -29 Various cytokines have been implicated in the postoperative inflammatory response including interleukin-1, interleukin-6, and tumor necrosis factor ␣, 30 and an increased C-reactive protein level.…”
Section: Incidence Morbidity and Mortality Of Perioperative Stroke mentioning
confidence: 99%